UPAYA MENINGKATKAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN INDUKTIF - Nurfaridah, Dais; Aminy, Fadlilah Aisah; Hanifunni`'am, Fanny Fauzy (Bestari, 2019)
This research is motivated by the low student learning outcomes of class III SDN 2 Cidolog, Cidolog Subdistrict, Ciamis Regency on the Subject of Science as an effort to improve student learning outcomes by using the Inductive Learning Model. Class management can be done with a varied and fun learning model. The method used is the Kurt Lewin model class action research method, because the method is felt to be very suitable in natural science learning to learn about events that occur in nature. The data collection techniques used are observation, test or assessment techniques and description analysis techniques. The technique can be used as a reference in learning, especially in learning science. After conducting research, the results obtained are 1) the ability of teachers in designing science learning planning to reach an average value of 91.93. 2) the teacher's skills in implementing science learning reaches an average value of 91.3. 3) while student learning outcomes reach an average value of 86.11 in the range of 94% with complete criteria of 17 students out of 18 students. This proves that increasing student learning outcomes can be implemented by increasing teacher skills both in planning and implementing learning. The learning referred to is the Inductive Learning Model, which means the results of the analysis show that the proposed hypothesis can be accepted.